A SURVEY ON CURRENT TRENDS IN PRIMARY TOOTH PULPOTOMY IN KARACHI - Lone, Maham Muneeb; Khan, Farhan Raza; Lone, Muneeb Ahmed; Rehman, Munawar (Journal of Ayub Medical College Abbottabad, 2015)
Background: In comparison to USA and United Kingdom where Paediatric Dentistry is considered a separate specialty; there very few formal teaching programs in Pakistan for Paediatric Dentistry. Many surveys have been carried out internationally,but no survey has been carried out locally to ascertain practice of dentists when treating paediatric patients. Therefore, it appears important to map features of Paediatric Dentistry practice in our country. The purpose of this study was to assess practice regarding pulpotomy of primary teeth among dentists of Karachi and to compare difference in pulpotomy practice of primary teeth between private practitioners and teaching dentists. Methods: Questionnaire was distributed by hand to dentists working in private clinics and teaching hospitals of Karachi, involved in treating primary teeth of children. Questions captured information on aspects related to pulpotomy procedure as carried out by dentists. Descriptive statistics and frequency distribution were computed. Chi-square test was applied to compare difference between dentists working in teaching hospitals versus private practitioners. Level of significance was kept at 0.05. Results: Although majority of dentists use the preferred medicament for pulpotomy, i.e., formocresol, it was seen that only a small proportion reported frequent use of radiographs and rubber dam. There was a significant difference in selecting post pulpotomy restorations for anterior teeth by teaching dentists (Composites) compared to private practitioners (who favoured GIC). Only 20-27% of dentists reported use of stainless steel crown for definitive restoration after pulpotomy. Conclusions: Although majority of dentists use formocresol as a preferred medicament for pulpotomy, it was seen that only a small proportion of participants reported frequent use of radiographs, rubber dam and stainless steel crowns which is far below the standard of care.